Advanced THz Optical Sensor for Ethanol and Benzene Detection: A Step towards Safer Industrial and Environmental Monitoring - Md. Abir Hossain; Md. Abir Hossain; Md. Anowar Kabir; Monir Morshed; Shuvo Sen (Sensing and Bio-Sensing Research, 2025)
Ethanol and Benzene are harmful to climate change, the human body, biodiversity, and long-term ecosystem balance. Normally, ethanol is added to gasoline, which causes climate change, and benzene is used in industries, which can cause cancer. Therefore, it is crucial to accurately identify both ethanol and benzene to ensure people's safety in the environment. This study shows a new and powerful photonic crystal fiber (PCF) sensor that uses terahertz (THz) technology. This sensor is designed to detect ethanol and benzene with high accuracy. The sensor works better because it has a special shape with a six-sided (hexahedron) center and a hexagonal outer cladding layer. According to our experiments, at 2.2 THz, the PCF sensor achieves relative sensitivities of 96.35 % for ethanol and 97.05 % for benzene. Effective Material Loss (EML), Effective Area, and Confinement Loss (CL) for ethanol and benzene are 0.0032 cm−1 and 0.0024 cm−1, 6.88 × 10−8 m2 and 7.79 × 10−8 m2 respectively, and 1.84 × 10−7 dB/m and 1.89 × 10−7 dB/m respectively, with operating frequency at 2.2 THz. There are various traditional detection techniques to detect those chemicals, but this proposed optical sensor performs better. So, the proposed PCF sensor demonstrates high sensitivity in simulation and indicates promising potential for future application in industrial safety and environmental monitoring.